Legal Protection for Health Insurance Policyholders Against Claim Denials Due to Non-Transparent Information in Insurance Policies - Stepanes, Erich; Basani, Christin Septina (Jurnal Indonesia Sosial Sains, 2026)
Health is a necessity for everyone, regardless of socioeconomic status, and health insurance is essential to ensure access to quality medical services while mitigating the financial impact of accidents and illnesses. In Indonesia, a common issue with insurance is the lack of customer understanding of policy terms, leading to misunderstandings. Legal Protection for Health Insurance Policyholders Against Claim Denials Due to Non-Transparent Information in Insurance Policies includes several measures. Customers should actively ask agents and insurance companies for clear explanations of policy terms, carefully review the policy before signing, and contact the Financial Services Authority (OJK) or the Consumer Dispute Settlement Board (BPSK) for mediation. If these steps fail, customers can resort to civil lawsuits. Legal remedies for failed claims involve understanding one’s rights, gathering relevant evidence, seeking written clarification from the insurance company about the claim rejection, and filing an official complaint to OJK. If the issue remains unresolved, the customer can pursue legal action in court.